Precursor slurry and lithium-sulfur battery positive electrode prepared from precursor slurry
By using a precursor slurry containing polyaniline in lithium sulfur batteries, the structural damage problem caused by volume expansion of lithium sulfur batteries is solved, the cycle stability and electrochemical performance of the battery are improved, and the battery life is extended.
Patent Information
- Application Number
- CN202411406480.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the charging and discharging process, the volume changes caused by the density differences between active sulfur and Li2S destroy the electrode structure, resulting in rapid attenuation of specific capacity and poor circulation stability, especially in soft-pack batteries.
Lithium sulfur is prepared by pretreatment, vacuum drying and rolling pressing using precursor slurry, including S/C composite positive electrode material, conductive agents Super-P, CNTs, polyaniline (PANI) with self-healing effect and binder LA133. The positive electrode of the battery uses PANI's self-healing function to repair the volume expansion of the positive electrode sheet during charging and discharging.
It improves the cycle life and electrochemical performance of lithium-sulfur batteries, extends the service life of the battery, and significantly improves the stability and capacity retention rate of the battery during the cycle.
Smart Images

Figure CN119315035A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a precursor slurry and a lithium-sulfur battery positive electrode prepared therefrom. Background Art
[0002] With the development of society and the continuous consumption of non-renewable energy such as fossil energy, more clean energy utilization methods have emerged, such as solar energy, tidal energy and wind energy. However, these energy sources have always been intermittent, and people have converted these renewable and clean energy into electrical energy for secondary use. As one of the most representative clean energy storage technologies, secondary batteries have attracted widespread attention. This rechargeable ion battery allows people to better utilize clean energy through cycles between charging and discharging.
[0003] As the most representative secondary battery, lithium-ion batteries are currently unable to meet the significant increase in energy density requirements. Lithium-sulfur batteries (sulfur is the positive electrode active material and lithium metal is the negative electrode) are used when the unit mass of elemental sulfur is completely converted into S 2- The theoretical specific capacity is as high as 1675 mAh g -1 , energy density can be as high as 2600Wh kg -1 , which is 7-8 times the energy density of current lithium-ion batteries. As the active material of the positive electrode of lithium-sulfur batteries, sulfur has the advantages of less environmental pollution, large reserves in nature, and low cost. Therefore, lithium-sulfur batteries have become the focus of current research and development of electric vehicle power batteries (secondary batteries). However, although lithium-sulfur batteries can theoretically achieve up to 2660Wh kg -1 The ultra-high energy density of lithium-sulfur batteries is far from the theoretical value in practical applications. Therefore, the preparation of high energy density lithium-sulfur batteries has become the key direction of lithium-sulfur battery application research.
[0004] During the charge and discharge process, the density difference between active sulfur and Li2S is large, resulting in a large volume change (76%). This may damage the electrode structure, leading to rapid attenuation of specific capacity, low utilization of active sulfur, and poor battery cycle stability leading to electrode material shedding. This volume expansion effect is more serious in soft-pack batteries, which will significantly damage the structure of the electrode. Summary of the invention
[0005] The purpose of the present invention is to provide a precursor slurry and a lithium-sulfur battery positive electrode prepared therefrom, so as to solve the above-mentioned technical problems.
[0006] To achieve the above object, the present invention provides a precursor slurry, comprising the following components: S / C composite positive electrode material, conductive agent Super-P, CNTs, PANI and binder LA133.
[0007] Since the precursor solution contains PANI which has a certain self-repairing effect, the precursor solution has a certain repair function.
[0008] The present invention also provides a method for preparing a precursor slurry, comprising:
[0009] Dissolving the binder LA133 in deionized water to obtain a first solution;
[0010] Add the S / C composite positive electrode material, the conductive agent Super-P, CNTs and PANI into the first solution, mix them evenly and obtain the precursor slurry.
[0011] Since the precursor solution contains PANI which has a certain self-healing effect, the precursor slurry synthesized based on PANI also has a self-healing effect.
[0012] The present invention also provides a method for preparing a positive electrode of a lithium-sulfur battery, comprising:
[0013] Pre-treating the precursor slurry to obtain a pre-treated slurry;
[0014] The pretreated slurry is coated on both sides of the positive electrode current collector, and after coating, vacuum drying and roller pressing are performed to obtain the positive electrode of the lithium-sulfur battery;
[0015] Wherein, the positive electrode current collector is made of aluminum.
[0016] Since the precursor slurry contains PANI, it has a self-repairing effect. Therefore, during the positive electrode charging and discharging process, the volume expansion of the positive electrode sheet can be repaired to a certain extent, which can improve the cycle life of the battery.
[0017] The present invention also provides a method for assembling a lithium-sulfur soft-pack battery using a lithium-sulfur battery positive electrode, comprising:
[0018] The lithium metal and the negative electrode current collector are compounded to obtain a copper-lithium composite tape, and the negative electrode sheet is obtained by die-cutting;
[0019] Die-cutting the positive electrode of the lithium-sulfur battery to obtain a positive electrode sheet;
[0020] The positive electrode sheet and the negative electrode sheet are stacked in a Z shape, the positive electrode sheet and the negative electrode sheet are separated by a polypropylene separator, and the positive and negative electrode tabs are welded respectively to obtain a battery cell;
[0021] The battery cell is placed in an aluminum-plastic film packaging shell for edge sealing and electrolyte injection, and finally vacuum packaged to obtain a lithium-sulfur soft-pack battery;
[0022] Wherein, the negative electrode current collector is made of copper; and the positive electrode of the lithium-sulfur battery is obtained through precursor slurry.
[0023] Since the precursor slurry contains PANI, it has a self-healing effect, so the battery prepared by the precursor slurry has a better cycle life.
[0024] The present invention also provides a lithium-sulfur soft-pack battery prepared based on the method of assembling a lithium-sulfur soft-pack battery using a lithium-sulfur battery positive electrode, wherein the lithium-sulfur battery positive electrode is obtained through a precursor slurry.
[0025] Since the precursor slurry contains PANI, it has a self-healing effect, so the battery cycle life obtained by using the precursor slurry is better.
[0026] Technical effects and advantages of the present invention:
[0027] PANI (polyaniline) has a certain self-healing effect due to the existence of hydrogen bonds and electrostatic interaction forces. During the positive electrode charge and discharge process, it can repair the volume expansion of the positive electrode sheet to a certain extent, which can improve the cycle life of the battery. Polyaniline also has excellent electrochemical properties and chemical stability, which can improve the electrochemical performance of lithium-sulfur batteries.
[0028] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a constant current charge and discharge cycle curve diagram of the battery in the comparative example;
[0030] Figure 2 It is a constant current charge and discharge cycle curve diagram of the battery in the embodiment. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportional relationship or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.
[0033] In order to solve the deficiencies of the prior art, the present invention discloses a precursor slurry, comprising the following components: S / C composite positive electrode material, conductive agent Super-P, CNTs, PANI and binder LA133.
[0034] Preferably, the mass ratio of the S / C composite positive electrode material, the conductive agent Super-P, CNTs, PANI and the binder LA133 is in the range of 7.5-9: 0.5-1.5: 0-0.5: 0.1-0.5: 0.5-1.5.
[0035] Among them, Super-P is preferably Super-P Li.
[0036] Polyaniline is added to the precursor slurry. Since polyaniline has hydrogen bonds and electrostatic interaction forces, the material has a certain self-healing effect. During the battery charging and discharging process, it can inhibit large volume expansion, thereby extending the battery cycle life.
[0037] The present invention also provides a method for preparing a positive electrode of a lithium-sulfur battery, comprising:
[0038] 1. Dissolve the binder LA133 in deionized water to obtain a first solution.
[0039] 2. Add S / C composite positive electrode material, conductive agent Super-P, CNTs, and PANI to the first solution, mix well to obtain precursor slurry. The mass ratio of S / C composite positive electrode material, conductive agent Super-P, CNTs, PANI, and binder LA133 is 7.5-9: 0.5-1.5: 0-0.5: 0.1-0.5: 0.5-1.5.
[0040] 3. Pre-treat the precursor slurry to obtain pre-treated slurry.
[0041] Specifically, the precursor slurry is stirred with a mixer (preferably a double-star vacuum mixer) under vacuum conditions to remove bubbles in the precursor slurry, wherein the parameters of the mixer include: a rotation speed of 30-110 rpm, a temperature of 25° C., and a pressure of -0.1 MPa.
[0042] 4. The pretreated slurry is coated on both sides of the positive electrode current collector. After coating, vacuum drying and roller pressing are performed to obtain the positive electrode of the lithium-sulfur battery.
[0043] Specifically include: using an intermittent experimental coating machine for coating, the coating speed is 100-300mmmin -1 The oven temperature during coating is 50-150°C. After double-sided coating is completed, it is dried in an oven at a temperature of 40-100°C for 12-24 hours. A hydraulically balanced electric roller machine is used for rolling, and the compaction density is 0.5-1g cm -3 .
[0044] Wherein, the positive electrode current collector is aluminum foil, porous aluminum foil or carbon-coated aluminum foil.
[0045] Among them, the active sulfur loading of the positive electrode of the lithium-sulfur battery is 2-4 mg cm -2 , single-sided coating thickness is 200-1000μm.
[0046] PANI (polyaniline) has a certain self-repairing effect due to the existence of hydrogen bonds and electrostatic interaction forces. During the positive electrode charge and discharge process, it can repair the volume expansion of the positive electrode sheet to a certain extent, which can improve the cycle life of the battery. Polyaniline also has excellent electrochemical properties and chemical stability, which can improve the electrochemical performance of lithium-sulfur batteries.
[0047] The present invention also provides a method for assembling a lithium-sulfur soft-pack battery using a lithium-sulfur battery positive electrode, comprising:
[0048] 1. Compounding lithium metal and negative electrode current collector to obtain copper-lithium composite tape, and then die-cutting to obtain negative electrode sheet;
[0049] 2. Die-cut the positive electrode of the lithium-sulfur battery to obtain the positive electrode sheet;
[0050] 3. The positive electrode sheet and the negative electrode sheet are stacked in a Z shape, the positive electrode sheet and the negative electrode sheet are separated by a polypropylene (PP) separator, and the positive and negative electrode tabs are welded respectively to obtain a battery cell;
[0051] Among them, the PP diaphragm needs to be dried at 40-100℃ for 12-24h in advance.
[0052] 4. Place the battery cell into an aluminum-plastic film packaging shell for edge sealing and electrolyte injection, and finally vacuum package to obtain a lithium-sulfur soft-pack battery;
[0053] Specifically, it includes: placing the battery cell into an aluminum-plastic film packaging shell for edge sealing and first electrolyte injection, and obtaining an initial lithium-sulfur soft-pack battery after vacuum packaging; forming the initial lithium-sulfur soft-pack battery, and then injecting the electrolyte for a second time, and obtaining a lithium-sulfur soft-pack battery after vacuum packaging.
[0054] The E / S ratios of the first and second injected electrolytes were 1-15 μL mg -1 and 1-5 μL mg -1 The final lithium-sulfur soft-pack battery needs to be aged for 6-48 hours at room temperature 20-40℃.
[0055] Wherein, the negative electrode current collector is copper foil, porous copper foil or copper mesh.
[0056] In order to better explain the present invention, examples and comparative examples are provided below.
[0057] Comparative Example
[0058] Sources of materials in this comparative example: S / C composite positive electrode material was purchased from Changsha Research Institute of Mining and Metallurgy Co., Ltd., conductive agent Super-P, preferably conductive agent Super-P Li purchased from Swiss Termeco, CNTs and binder LA133 were purchased from Cyber Electrochemical Materials Network, and PANI was purchased from McLean.
[0059] This embodiment provides a method for assembling a lithium-sulfur soft-pack battery, comprising the following steps:
[0060] 1. Take 66.67 g of LA133 emulsion with a solid content of 15% (i.e., 10 g of LA133) and dissolve it in 200 ml of deionized water. Use a double planetary vacuum mixer to homogenize LA133 in deionized water at 30 rpm for 30 min.
[0061] 2. Add 5 g of conductive agent Super-P Li to the uniformly mixed dispersion obtained in step 1, and stir at 30 rpm for 30 min in a double planetary vacuum mixer to fully wet the conductive agent Super-P Li.
[0062] 3. Then, 3 g of CNTs were added to the dispersion kettle in batches and stirred at 30 rpm for 30 min.
[0063] 4. Add 80 g of S / C composite positive electrode material to the solution obtained in step 3 in 2-3 batches to fully wet it, and stir at a high speed of 100 rpm for 12 hours.
[0064] 5. Continue to vacuum (-0.1Mpa) and stir at 100rpm for 2h to remove bubbles and obtain a uniformly mixed positive electrode slurry.
[0065] 6. The positive electrode slurry after ultrasonic treatment in step 5 was coated on the front and back of aluminum foil with an intermittent test coater at an oven drying temperature of 100°C and a coating speed of 100 mm / min to a thickness of 400 μm (single-side thickness) to obtain 2.24 mg cm -2 Surface load of the pole piece.
[0066] 7. After coating, the electrode is vacuum dried at 60°C for 12 hours.
[0067] 8. The copper-lithium composite strip with lithium plating on both sides is used as a negative electrode, and the thickness of the lithium layer on one side is 80μm.
[0068] 9. Place the polypropylene (PP) diaphragm in a constant temperature box at 60°C for 12 hours.
[0069] 10. Cut the positive and negative electrode sheets obtained in step 7 and step 8 into pieces with a size of 58×45 mm using a semi-automatic die-cutting machine in a glove box. 2 The pole piece.
[0070] 11. The positive and negative electrode sheets prepared in step 10 and the polypropylene (PP) separator dried in step 9 are stacked in a certain order, and the positive and negative electrode ears are welded with a spot welding machine after stacking to obtain a battery cell.
[0071] 12. Place the battery cell obtained in step 11 into an aluminum-plastic film outer packaging shell for edge sealing, liquid injection, and vacuum packaging to obtain a soft-pack lithium-sulfur battery.
[0072] 13. In this embodiment, the positive electrode surface loading of the soft-pack battery obtained in step 12 is 2.24 mg cm -2 The battery is assembled with nine layers of positive electrode and eight layers of negative electrode. The total active mass of the battery is 1.87g, the electrolyte content is 1870μL, and the electrolyte is 1.0MLiTFSI in DME:DOL=1:1Vol%with2.0%LiNO3.
[0073] 14. The battery obtained in step 12 is aged at a constant temperature of 25°C for 12 hours.
[0074] See also Figure 1 The figure shows that the surface loading in this comparative example is 2.24 mg cm -2 The constant current charge-discharge cycle curve of the assembled nine-layer positive electrode and eight-layer negative electrode soft-pack battery. At a rate of 0.5C, the discharge capacity of the soft-pack battery is 654.8mAh g -1 After 50 cycles, the discharge capacity decayed to 508.92 mAh g -1 The capacity retention rate is 77.73%, the capacity decay rate per cycle is 0.45%, the coulombic efficiency during the battery cycle is about 90%, and Figure 1 It can be seen that the cycle performance is good in the first 30 cycles, and the capacity decay is more obvious in the last 20 cycles. This is because the positive electrode undergoes a large volume expansion during the cycle, which causes the active sulfur to fall off the positive electrode current collector.
[0075] Example
[0076] In order to compare and illustrate the role of the PANI self-healing material added in the present invention in the lithium-sulfur battery, the method for preparing the positive electrode slurry in this embodiment is basically the same as that in the comparative example, the only difference is that 2g of PANI is also added during the slurry mixing process in step 4, that is, the masses of the S / C composite positive electrode material, the conductive agent Super-P Li, the CNTs, the PANI and the adhesive LA133 in the adhesive LA133 emulsion in the positive electrode slurry are 80g, 5g, 3g, 2g and 10g, respectively.
[0077] Figure 2 In this example, the surface loading of PANI auxiliary material is 2.24 mg cm -2 The constant current charge-discharge cycle curve of the assembled nine-layer positive electrode and eight-layer negative electrode soft-pack battery. As can be seen from the figure, at a rate of 0.5C, the discharge capacity of the soft-pack battery is 680.1mAh g -1 After 100 cycles, the discharge capacity decayed to 635.02 mAh g -1 The capacity retention rate is 93.4%, the capacity attenuation rate is 0.07%, the coulombic efficiency during the battery cycle is around 95%, and the cycle stability is greatly improved, especially in the cycle after 30 cycles.
[0078] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A precursor slurry for a lithium-sulfur battery positive electrode, characterized in that: The invention comprises the following components: S / C composite positive electrode material, conductive agent Super-P, CNTs, PANI and binder LA133.
2. The precursor slurry according to claim 1, characterized in that: The mass ratio of S / C composite positive electrode material, conductive agent Super-P, CNTs, PANI and binder LA133 ranges from 7.5-9: 0.5-1.5: 0-0.5: 0.1-0.5: 0.5-1.
5.
3. A method for preparing the precursor slurry according to claim 1, characterized in that: include: Dissolving the binder LA133 in deionized water to obtain a first solution; Add the S / C composite positive electrode material, the conductive agent Super-P, CNTs and PANI into the first solution, mix them evenly and obtain the precursor slurry.
4. A method for preparing a positive electrode for a lithium-sulfur battery based on the precursor slurry according to claim 1, characterized in that: include: Pre-treating the precursor slurry to obtain a pre-treated slurry; The pretreated slurry is coated on both sides of the positive electrode current collector, and after coating, vacuum drying and roller pressing are performed to obtain the positive electrode of the lithium-sulfur battery; Wherein, the positive electrode current collector is made of aluminum.
5. The method according to claim 4, characterized in that The positive electrode current collector is aluminum foil, porous aluminum foil or carbon-coated aluminum foil.
6. The method according to claim 4, characterized in that Pre-treating the precursor slurry, including: stirring the precursor slurry with a stirrer under vacuum conditions to remove bubbles in the precursor slurry; The parameters of the mixer include: a rotation speed of 30-110 rpm and a temperature of 20-25°C.
7. The method according to claim 4, characterized in that The pretreated slurry is coated on both sides of the positive electrode current collector, including: coating using an intermittent experimental coating machine; Among them, the coating speed is 100-300mm min -1 , the oven temperature during coating is 50-150℃.
8. The method according to claim 4, characterized in that The active sulfur loading of the positive electrode of lithium-sulfur battery is 2-4 mg cm -2 , single-sided coating thickness is 200-1000μm.
9. The method according to claim 4, characterized in that The drying parameters include: drying in an oven at 40-100°C for 12-24 hours; the roller pressing parameters include: compaction density of 0.5-1 g cm -3 .
10. A method for assembling a lithium-sulfur soft-pack battery from a lithium-sulfur battery positive electrode as claimed in any one of claims 4 to 9, characterized in that: include: The lithium metal and the negative electrode current collector are compounded to obtain a copper-lithium composite tape, and the negative electrode sheet is obtained by die-cutting; Die-cutting the positive electrode of the lithium-sulfur battery to obtain a positive electrode sheet; The positive electrode sheet and the negative electrode sheet are stacked in a Z shape, the positive electrode sheet and the negative electrode sheet are separated by a polypropylene separator, and the positive and negative electrode tabs are welded respectively to obtain a battery cell; The battery cell is placed in an aluminum-plastic film packaging shell for edge sealing and electrolyte injection, and finally vacuum packaged to obtain a lithium-sulfur soft-pack battery; Wherein, the negative electrode current collector is made of copper; and the positive electrode of the lithium-sulfur battery is obtained by the precursor slurry according to claim 1.
11. The method according to claim 10, characterized in that The negative electrode current collector is copper foil, porous copper foil or copper mesh.
12. The method according to claim 10, characterized in that The battery cell is placed in an aluminum-plastic film packaging shell for edge sealing and electrolyte injection, and finally vacuum packaged to obtain a lithium-sulfur soft-pack battery, including: The battery cell is placed in an aluminum-plastic film packaging shell for edge sealing and first electrolyte injection, and then vacuum packaged to obtain an initial lithium-sulfur soft-pack battery; The initial lithium-sulfur soft-pack battery is formed, and then the electrolyte is injected for a second time, and the lithium-sulfur soft-pack battery is obtained after vacuum packaging.
13. The method according to claim 12, characterized in that The E / S ratios of the first and second injections of the electrolyte were 1-15 μL mg -1 and 1-5 μL mg -1 .
14. The method according to claim 10, characterized in that The polypropylene diaphragm needs to be dried at 40-100℃ for 12-24h in advance.
15. The method according to claim 10, characterized in that The method further comprises: placing the lithium-sulfur soft-pack battery at a room temperature of 20-40° C. for aging for 6-48 hours.
16. A lithium-sulfur soft-pack battery prepared by the method for assembling a lithium-sulfur soft-pack battery using a lithium-sulfur battery positive electrode as claimed in any one of claims 10 to 15, characterized in that: The lithium-sulfur battery positive electrode is obtained by the precursor slurry according to claim 1.
Citation Information
Patent Citations
Preparation method of lithium-sulfur battery positive electrode and method for assembling soft package battery by using lithium-sulfur battery positive electrode
CN114975881A
Self-repairing flexible electrode, preparation method thereof and lithium-sulfur battery
CN115275096A
Silicon nanowire electrode, preparation method thereof and lithium ion battery containing silicon nanowire electrode
CN117747742A
Seal-healing composites and applications thereof
US20160049217A1